Case report: Late in-stent thrombosis in a patient with vertebrobasilar dolichoectasia after stent-assisted coil embolization due to the discontinuation of antiplatelet therapy - Ji, Zhe; Yang, Wanxin; Ma, Yongjie; Bian, Lisong; Li, Guilin; Fu, Yongjuan; Piao, Yueshan; Zhang, Hongqi (Frontiers in Neurology, 2023)
Vertebrobasilar dolichoectasia (VBD) is a rare type of cerebrovascular disorder with high rates of morbidity and mortality. Due to the distinct pathological characteristics that fragmented internal elastic lamina and multiple dissections, VBD is difficult to treat and cured. Stent-assisted coil embolization is one of the main treatment modalities for such lesions. However, the duration of healing remained questionable, and there were no effective measures for evaluating endothelial coverage. Before complete endothelial coverage, the discontinuation of antiplatelet therapy may lead to fatal in-stent thrombosis; however, continued antiplatelet therapy could also result in bleeding complications. Thus, we present an autopsy case of late in-stent thrombosis due to the discontinuation of antiplatelet therapy and systematically review the literature to provide a reference for endovascular treatment and antiplatelet regimen of VBD.